The Impact of Generative AI on Clinical Decision-Support Systems: A Systematic Review of Applications, Benefits, and Ethical Challenges - Polampally, Sanjay Kumar; Ravindran, Renjith Kathalikkattil; Jeyabalan, Jeyashree; Kusam, Venugopala Reddy; Morsu, Ashok; Ragunayakula, Sharat Kumar (Universitas Muhammadiyah Yogyakarta, 2025)
This systematic literature review explores the integrations of generative artificial intelligence (AI) models, such as ChatGPT, GPT-4, MedPaLM, BioGPT, and LLaMA, into Clinical Decision Support Systems (CDSS) between 2020 and 2025. Analyzing 500 studies across multiple countries and healthcare contexts, the paper evaluates that generative AI transforms clinical workflows through enhanced diagnostic assistance, personalized treatment planning, improved patient communication, and document automation.